The perception of geography among the German population. Findings of a representative survey - Gans, Paul; Hemmer, Ingrid; Hemmer, Michael; Miener, Kim (ERDKUNDE, 2018)
Presented here is a representative study of the German population which collected information on the perception of geography as a school subject, as a science, and on the job market. The theoretical basis utilised for this purpose is a two-dimensional attitude research approach which comprises cognitive and affective aspects. The measuring instrument was theory-based and developed by a team of geographers. According to the findings of the study, the perception of geography - both that of the school subject as well as the science - can be classified as highly positive. Geography lessons are seen as a subject which promotes spatial orientation, but also as a subject dealing with human-environment relationships. The science geography is understood above all as the science of the relationship between humans and their environment. However, both in schools and in science, geography is more strongly linked to physical geography topics and topics that deals with human-environmental relationships than with human geography topics. Respondents see jobs for geographers as being mainly in two areas: environmental planning/risks/protection and urban/regional planning. The findings of the study support the proposition that the perception of geography is influenced relatively strongly by how geography is taught. Contact to geographers also has a significant influence on perception. The article concludes with a discussion of the most important results and an outlook on further research.